The wind of thinking. (June 2022) - Zittoun, Tania
The Life of the Mind (1978) opens with a reflection of thinking. By thinking, Hannah Arendt means our capacity to withdraw from the world so as to reflect about the meaning of things. Thinking is an activity with no results in itself: searching for meaning, it cannot reach a goal, as any meaning hence produced can only be questioned again. Thinking is made possible through imagination, and demands the use of language and metaphors. It also has to be part of a form of inner dialogue – a moment in which we become two-in-one. Hence, Arendt seems to define thinking as a dynamic, mediated dialogical process of meaning making. In this paper, I first situate Arendt's reflection on thinking within her life work. I then present her main propositions: that thinking is not knowing; that it demands a form of withdrawal; that it implies imagination; that it is mediated by language and metaphors; that it is a form of inner dialogue; and that it escapes time. Finally, I examine some of the implications of this approach to thinking for contemporary cultural psychology.